2005
DOI: 10.1243/095765005x31081
|View full text |Cite
|
Sign up to set email alerts
|

The impact of rotor labyrinth seal leakage flow on the loss generation in an axial turbine

Abstract: This paper examines the impact of labyrinth seal leakage flow over the rotor shroud on the loss generation in an axial turbine stage. Numerical studies have been carried out with an in-house solver using the Baldwin -Lomax turbulence model to identify the changes in secondary flow structures. The code has been validated for this application using test data from a low-speed axial turbine stage with a simple generic rotor shroud labyrinth seal. Numerical simulations are carried out with different clearance gaps … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 22 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…Thus, helicity was introduced to discern the secondary flow vortex and study the flow field in the vane. The helicity is the scalar product of the vorticity vector and the velocity of flow, which is also used by Torre [18], Anker [19] and Natkaniec [20] in their study to analyze the complex flow field caused by the secondary flow. In order to understand the evolution of secondary flow vortex in the passage, contours of helicity and isolines of stagnation pressure recovery coefficient are showed in a set of cross section, which locate at 5% C x upstream of the blade leading edge, 30%, 60%, 90% and 120% downstream of the blade leading edge successively.…”
Section: Analysis Of Numerical Resultsmentioning
confidence: 99%
“…Thus, helicity was introduced to discern the secondary flow vortex and study the flow field in the vane. The helicity is the scalar product of the vorticity vector and the velocity of flow, which is also used by Torre [18], Anker [19] and Natkaniec [20] in their study to analyze the complex flow field caused by the secondary flow. In order to understand the evolution of secondary flow vortex in the passage, contours of helicity and isolines of stagnation pressure recovery coefficient are showed in a set of cross section, which locate at 5% C x upstream of the blade leading edge, 30%, 60%, 90% and 120% downstream of the blade leading edge successively.…”
Section: Analysis Of Numerical Resultsmentioning
confidence: 99%
“…The yþ (of the closest grid point from wall) is around 2 in the blade and endwall surfaces. Anker et al 40,41 made a comparison of unsteady and steady simulations about the interactions of the leakage flow and the main flow in the shrouded turbine. The results have shown that it is perfectly sufficient to conduct steady-state simulations in order to capture the average rotor leakage flow effects.…”
Section: Numerical Techniquementioning
confidence: 99%
“…The influence of the one-sided shroud seal composed of two disks on the flow in axial low-speed turbine passages has been analysed in [2,3]. Among other issues, these works examined experimentally the influence of the leakages on the mixing loss and secondary flows.…”
Section: Introductionmentioning
confidence: 99%